Analysis Implementation of Total Quality Management System on Operational Performance: Case Study on Fast Moving Consumer Goods Company - Badawi, Yessica Tania. H; Arviansyah, Arviansyah (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2025)
Implementation of the Total Quality Management System in food companies is essential to help company produce quality product for consumers and to gain competitive advantage. This research aims to analyze TQMS implementation in Fast Moving Consumer Goods companies that produce food and beverages regarding operational performance. The data collected from 136 respondents, who are employees in the FMCG sector, was analyzed using a quantitative method with PLS-SEM. The endogenous variable in this study is operational performance, while the exogenous variables are dimensions of TQM practices, which include leadership, employee involvement, customer focus, strategic planning, and continuous improvement. The results of the study indicate that the implementation of TQM in the factors of leadership, employee involvement, customer focus, and continuous improvement has a positive and significant impact on operational performance. In contrast, strategic planning does not have a significant positive impact on the operational performance of the company.